Women in Prison: Self-Injurious Behavior, Risk Factors, Psychological Function, and Gender-Specific Interventions. (September 2014) - Wakai, Sara; Sampl, Susan; Hilton, Laura; Ligon, Beyonka
Treating self-injurious behavior (SIB) is a challenge in any environment. There is an increased level of complexity when this type of behavior occurs in a female correctional facility. This article focuses on SIB in incarcerated women, including the importance of identifying risk factors, understanding the psychological functions of SIB, addressing the influence of gender on treatment, and acknowledging challenges unique to the correctional environment. Treatment recommendations specific to incarcerated females, such as motivational interviewing and a cognitive behavioral approach, provide guidance to address the underlying causes of SIB and the development of healthier coping behaviors for female inmates. Effective management of SIB in a female correctional facility simultaneously reduces the burden on staff and increases the safety of staff and inmates.